2011
DOI: 10.1049/iet-cta.2009.0436
|View full text |Cite
|
Sign up to set email alerts
|

Separation principle for networked control systems with multiple-packet transmission

Abstract: Abstract:The authors investigate a class of observer-based discrete-time networked control systems (NCSs) with multiple-packet transmission where random packet dropouts occur independently in both the sensor-to-controller (S/C) and controller-to-actuator (C/A) channels. The authors first propose and prove the separation principle for the NCSs where packet dropouts in the C/A and S/C channels are governed by two independent Markov chains, respectively. Secondly, the authors derive a sufficient condition, in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The authors of [23,24] proved that the separation principle holds for networked control systems with a triangular structure such as the one that has the dynamic matrix A CL kC1 . This implies that the observer and controller can be designed independently to achieve a mean square stable behaviour, and thus guaranteeing the mean square stability of the closed loop system.…”
Section: Closed Loop Analysismentioning
confidence: 99%
“…The authors of [23,24] proved that the separation principle holds for networked control systems with a triangular structure such as the one that has the dynamic matrix A CL kC1 . This implies that the observer and controller can be designed independently to achieve a mean square stable behaviour, and thus guaranteeing the mean square stability of the closed loop system.…”
Section: Closed Loop Analysismentioning
confidence: 99%
“…In Peñarrocha et al (2005), Wu et al (2011), Gawthrop and Wang (2011) the separation principle for observer-based NCS systems that present a triangular structure was demonstrated, leading to an independent design of the observer and the controller gains. Furthermore, the work Wu et al (2010) demonstrated that the mean square stability of NCS systems with a time varying model that is only updated when successful transmissions occurs is equivalent to the mean square stability at the (fast) control period.…”
Section: Closed Loop Dynamics Analysismentioning
confidence: 99%
“…Firstly, since time delay and packet dropout usually exist simultaneously in the real network, it is important to establish a model to handle them in a common framework. Various modeling methods have been proposed including time delay system model [11], switched system model [12][13][14], asynchronous dynamical system model [15,16], and stochastic system model [6,8,9,[17][18][19][20][21][22][23][24][25]. Among them, stochastic system model becomes popular in recent years and one of the most 2 Complexity used ways is to adopt a Markov discrete-time linear system to describe random time delay or packet dropouts [9, 20-22, 24, 25].…”
Section: Introductionmentioning
confidence: 99%